Renal Effects of Graphite Oxide Sheets in Albino Rats (Rattus norvegicus): A Preliminary Study - Ambar N. Muhammad; Ayesha Ijaz; Adeel Khalid; Khuram Rafique; Rabia Tabassum; Aqeela Zahra; Muhammad Danish; Hina Tariq; Mochammad A. Herdiansyah; Arif N. M. Ansori (BIO Integration)
Although diamond-like carbon-coated joint replacements are widely recommended for full bone replacements in humans, their clinical application is substantially limited by contamination with wear particles, specifically graphite nanoparticles, which are cytotoxic. This study was aimed at assessing the adverse effects of graphite oxide (GO) sheets on the blood and renal tissues of adult male albino rats. A total of 25 albino rats were procured from the Government College University Faisalabad, Punjab, Pakistan, and acclimated for 7 days in well-ventilated enclosures, after approval from the ethical committee at the University of Sialkot. The rats were randomly assigned to the following groups: a control group receiving no treatment, a vehicle control group receiving normal saline, and three treatment groups (G1, G2, and G3, administered GO nanosheets at doses of 5, 6, or 7 mg/kg body weight, respectively). Treatments were delivered through intraperitoneal injection on alternating days over 28 days. Animal mortality, hematological parameters, and kidney histology were assessed. The control and vehicle control groups showed normal findings, whereas the groups exposed to GO exhibited highly significant pathological changes in renal function tests (p<0.05). Histological alterations were more severe in the moderate- and high-dose treatment groups than the low-dose group, which displayed typical histological features. The treatment groups exhibited various histological changes, including vacuolation, renal fibrosis, inflammation, and tubular damage, which were significantly more pronounced in the G2 and G3 groups than the G1 group. Thus, exposure to GO sheets resulted in detrimental effects on renal tissues in albino rats. The findings suggested that the investigated doses of GO have detrimental effects on the health of living organisms.